Pyramiodontherium Rovereto (Xenarthra, Tardigrada, Megatheriinae) from the Early Pliocene of San Fernando, Catamarca Province, Argentina - Bonini, Ricardo Adolfo (2015)
A tibia-fibula referred to Pyramiodontherium Rovereto (Xenarthra, Tardigrada, Megatheriinae) from the Zanclean Stage (Early Pliocene) of San Fernando, Catamarca Province, Argentina is described.